2010
DOI: 10.1088/0004-637x/709/2/1249
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Down of the Long-Period Accreting Pulsar 4u 2206+54

Abstract: 4U 2206+54 is a high mass X-ray binary which has been suspected to contain a neutron star accreting from the wind of its companion BD +53 • 2790. Reig et al. (2009) have recently detected 5560 s period pulsations in both RXTE and INTEGRAL observations which they conclude are due to the spin of the neutron star. We present observations made with Suzaku which are contemporaneous with their RXTE observation of this source. We find strong pulsations at a period of 5554 ± 9 s in agreement with their results. We als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 31 publications
4
57
0
Order By: Relevance
“…Some models predict the system 4U 2206+543 to harbour a magnetar (see, e.g. Finger et al, 2010). In addition to the spectral model typical for X-ray pulsars (power law with high energy cut-off), some evidence of a cyclotron resonance scattering feature at energies ∼ 30 and ∼ 60 keV were presented using RXTE, BeppoSAX (Torrejón et al, 2004), and INTEGRAL (Blay et al, 2005;Wang, 2009) data.…”
Section: High-mass X-ray Binaries In the Milky Way 71mentioning
confidence: 99%
“…Some models predict the system 4U 2206+543 to harbour a magnetar (see, e.g. Finger et al, 2010). In addition to the spectral model typical for X-ray pulsars (power law with high energy cut-off), some evidence of a cyclotron resonance scattering feature at energies ∼ 30 and ∼ 60 keV were presented using RXTE, BeppoSAX (Torrejón et al, 2004), and INTEGRAL (Blay et al, 2005;Wang, 2009) data.…”
Section: High-mass X-ray Binaries In the Milky Way 71mentioning
confidence: 99%
“…For instance, Finger et al (2010) interpreted 4U 2206+54 (P s ∼ 5560 s) as an accreting magnetar. Efforts to explain the long period pulsars by alternative models are accumulating: Ikhsanov (2007) incorporated a subsonic propeller state into the evolutionary tracks of NSs, which can overcome the spin period barrier of ∼ 500 s; Wang & Chang (2012) proposed a retrograde wind accretion to explain long spin periods of supergiant fast X-ray transients (see also Christodoulou et al 2017); suggested a magnetized accretion stream to explain the long spin period of 4U 2206+54 where the magnetic field at the surface of the NS is expected to be ∼4×10 12 G; Shakura et al (2012Shakura et al ( , 2013 developed a model for quasi-spherical subsonic accretion, which can explain long spin periods of the NSs in symbiotic XRBs.…”
Section: See Section 43)mentioning
confidence: 99%
“…However, there are some metallic lines typical for a later-type spectrum (Negueruela & Reig 2001). The compact object is a neutron star (Torrejón et al 2004) with spin period P s = 5554±9 s (Finger et al 2010). The X-ray spectrum of 4U 2206+54 is typical for a neutron star accreting material onto its magnetic poles.…”
Section: U 2206+54 (Bd 53mentioning
confidence: 99%